Method for producing titanium-rich direct reduced iron and high-titanium slag by using vanadium titano-magnetite
By preparing iron-titanium concentrate composite high-titanium pellets and applying gas-based vertical furnace direct reduction process, the problem of waste of titanium resources and high energy consumption in vanadium titanium magnetite in vanadium titanium magnetite is solved, and efficient recycling of titanium resources and improving product quality is achieved.
Patent Information
- Application Number
- CN202411673934.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
In the existing comprehensive utilization process of vanadium titanium magnetite resources, the blast furnace-converter process leads to waste of TiO2 resources, and the pre-reduction-electric furnace process has problems such as high energy consumption, large CO2 emissions, low production capacity and poor product quality.
By making vanadium-titanium magnetite into vanadium-titanium iron concentrate powder and titanium concentrate powder and mixed with binder, iron-titanium concentrate composite high-titanium pellets are prepared, and titanium-rich direct reduction process is used to produce titanium-rich direct reduction iron, providing high-quality titanium-rich raw materials for melting and dispersing furnace smelting titanium slag.
It has achieved efficient recovery of titanium resources in vanadium titanium magnetite, improved the grade of TiO2 in the titanium slag of electric furnaces, reduced CO2 emissions, reduced energy consumption, and improved product quality.
Smart Images

Figure CN119506503A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ironmaking, specifically to the technical field of comprehensive utilization of vanadium-titanium magnetite resources, and in particular to a method for producing titanium-rich direct-reduced iron and high-titanium slag by utilizing vanadium-titanium magnetite. Background Art
[0002] The low-carbon and efficient utilization of titanium resources in vanadium-titanium magnetite is the key to the green development of the titanium-iron circular economy industrial chain. After beneficiation, vanadium-titanium magnetite can obtain vanadium-titanium iron concentrate and titanium concentrate. The current comprehensive utilization process of vanadium-titanium magnetite resources is mainly divided into the iron and vanadium extraction process of blast furnace-converter smelting vanadium-titanium iron concentrate and the titanium extraction process of pre-reduction-electric furnace smelting titanium concentrate. However, the TiO2 in the raw materials entering the "blast furnace-converter process" all enters the slag, forming a high-titanium slag with a TiO2 content of 22-25%, which is difficult to utilize as a resource, resulting in a huge waste of 54% of the total titanium resources, and at the same time causing a large amount of CO2 emissions. The "pre-reduction-electric furnace process" is a non-blast furnace smelting process with the advantages of high recovery of valuable elements and low environmental load. It has good application prospects for the low-carbon comprehensive utilization of complex paragenetic ores such as vanadium-titanium magnetite. However, the current coal-based direct reduction process mainly uses rotary kilns, rotary hearth furnaces and other coal-based direct reduction processes to pre-reduce titanium concentrate pellets, which has problems such as high energy consumption, large CO2 emissions, low production capacity and poor product quality. The gas-based vertical furnace direct reduction process has the advantages of cleanliness, high efficiency and stable product performance, and helps to improve the grade of TiO2 in subsequent titanium slag, becoming an important development direction of the vanadium-titanium magnetite pre-reduction process.
[0003] High-quality pellets are the basic guarantee for efficient and smooth gas-based vertical furnace direct reduction. However, vanadium-titanium magnetite is difficult to pelletize and roast due to its complex composition and structure, and is prone to expansion, pulverization, and adhesion during the reduction process. At present, the patents on the preparation process of vanadium-titanium pellets for gas-based vertical furnace direct reduction mainly include CN107058727A, CN103361481A, etc. Among them, patent CN107058727A uses vanadium-titanium magnetite ore as raw material, and patent CN103361481A uses vanadium-titanium iron concentrate as raw material. However, the process has problems such as low TiO2 content in the prepared pellets and difficulty in ensuring the grade of TiO2 in the subsequent electric furnace titanium slag. In terms of direct reduction of vanadium-titanium magnetite to recover valuable resources, patent CN109136588A provides a method for producing high-titanium slag by direct reduction of titanium concentrate in a gas-based vertical furnace. This method uses titanium concentrate as raw material to prepare pellets, which are applied to the direct reduction-induction furnace smelting process. Although it can obtain high-grade titanium slag, it cannot simultaneously achieve effective recovery of titanium resources in vanadium-titanium iron concentrate powder. Patent CN101575677A provides a method for producing titanium-rich materials and steel products using titanium ore. Although it can effectively recover various valuable elements in the surface ore, surface ore and weathered ore or titanium sand ore of vanadium-titanium magnetite, this method adds a carbonaceous reducing agent during the preparation of pellets, which will introduce ash to reduce the grade of titanium slag, and easily cause the titanium slag to form a large amount of glass phase, destroying the activity of titanium slag, and at the same time, it will produce CO2 pollutants during the pre-reduction process. Summary of the invention
[0004] In view of the shortcomings of the prior art mentioned above, the purpose of the present invention is to provide a method for producing titanium-rich direct-reduced iron using vanadium-titanium magnetite, by preparing iron-titanium concentrate composite high-titanium pellets that meet the requirements of gas-based vertical furnace direct reduction smelting, and applying them to gas-based vertical furnace direct reduction to produce titanium-rich direct-reduced iron, thereby providing high-quality titanium-rich raw materials for smelting titanium slag in smelting electric furnaces.
[0005] To achieve the above-mentioned object and other related objects, the present invention provides a method for producing titanium-rich direct-reduced iron using vanadium-titanium magnetite, comprising the following steps:
[0006] 1) Preparation of ferro-titanium concentrate composite high-titanium pellets:
[0007] The vanadium-titanium magnetite ore is made into vanadium-titanium iron concentrate powder and titanium concentrate powder;
[0008] The vanadium-titanium iron concentrate powder and the titanium concentrate powder are mixed with a binder to prepare iron-titanium concentrate composite green balls, and then oxidatively roasted to obtain iron-titanium concentrate composite high-titanium balls;
[0009] The compressive strength of the ferro-titanium concentrate composite high-titanium pellets is greater than 2000N / piece, and the reduction expansion rate is less than 20%;
[0010] 2) Direct reduction of ferro-titanium concentrate composite high-titanium pellets:
[0011] The ferro-titanium concentrate composite high-titanium pellets are subjected to a gas-based vertical furnace direct reduction process to obtain titanium-rich direct reduced iron with a metallization rate greater than or equal to 85%.
[0012] Furthermore, in step 1), the vanadium-titanium magnetite ore is crushed, ground, and sieved to obtain vanadium-titanium iron ore concentrate powder and titanium concentrate powder.
[0013] Furthermore, the vanadium-titanium iron concentrate powder meets at least one of the following indicators: by mass fraction, the powder with a particle size less than 0.074 mm accounts for greater than or equal to 80%, the total iron content is greater than or equal to 50%, and the TiO2 content is greater than or equal to 9%.
[0014] Furthermore, the titanium concentrate powder meets at least one of the following indicators: by mass fraction, the proportion of powder with a particle size less than 0.074 mm is greater than or equal to 80%, and the TiO2 content is greater than or equal to 45%.
[0015] Furthermore, the ferro-titanium concentrate composite green ball meets at least one of the following indicators: by mass fraction, the proportion of particles with a particle size of 8 to 16 mm is greater than or equal to 90%, and the moisture content is 7.5% to 10.5%.
[0016] Furthermore, in step 1), when preparing the iron-titanium concentrate composite green balls, the mass ratio of the vanadium-titanium iron concentrate powder to the titanium concentrate powder is 10-80:20-90.
[0017] Furthermore, in step 1), when preparing the iron-titanium concentrate composite green balls, the ratio of the total mass of the vanadium-titanium iron concentrate powder and the titanium concentrate powder to the mass of the binder is 100:1-2.
[0018] Furthermore, in step 1), in the ferro-titanium concentrate composite green ball, the mass ratio of the vanadium-titanium ferro-concentrate powder, the titanium concentrate powder and the binder is 10-80:20-90:1-2.
[0019] Furthermore, the vanadium-titanium-iron concentrate powder and the titanium concentrate powder are dried before being mixed with the binder; preferably, the drying conditions of the vanadium-titanium-iron concentrate powder and the titanium concentrate powder include at least one of the following conditions: a drying temperature of 150 to 300° C. and a drying time of 3 to 5 hours.
[0020] Furthermore, in step 1), the process of oxidatively roasting the ferro-titanium concentrate composite green pellets to obtain ferro-titanium concentrate composite high-titanium pellets includes preheating and roasting steps in sequence.
[0021] Furthermore, in step 1), the preheating conditions of the ferro-titanium concentrate composite green balls include at least one of the following conditions: a preheating temperature of 850 to 950° C. and a preheating time of 8 to 25 minutes.
[0022] Furthermore, in step 1), the roasting conditions of the ferro-titanium concentrate composite green balls include at least one of the following conditions: a roasting temperature of 1200 to 1350° C., a roasting time of 20 to 50 minutes, and an oxidizing atmosphere.
[0023] Furthermore, in step 1), before the preheating process, the ferro-titanium concentrate composite green balls are also dried; preferably, the drying conditions of the ferro-titanium concentrate composite green balls include at least one of the following conditions: a drying temperature of 150 to 300°C and a drying time of 2 to 5 hours.
[0024] Furthermore, in step 1), after roasting, the ferro-titanium concentrate composite high-titanium pellets are obtained by cooling.
[0025] Furthermore, in step 2), the gas-based vertical furnace direct reduction process conditions include at least one of the following conditions: a direct reduction temperature of 950 to 1050° C., and a direct reduction time of 3 to 5 hours.
[0026] Furthermore, in step 2), the ferro-titanium concentrate composite high-titanium pellets are first subjected to a spraying treatment, and then subjected to a gas-based vertical furnace direct reduction process to obtain titanium-rich direct reduced iron with a metallization rate greater than or equal to 85%.
[0027] Furthermore, in step 2), the ferro-titanium concentrate composite high-titanium pellets and reducing gas are subjected to a gas-based vertical furnace direct reduction process to obtain titanium-rich direct reduced iron with a metallization rate greater than or equal to 85%.
[0028] Furthermore, the reducing gas meets at least one of the following indicators: the volume ratio of H2 and CO is greater than or equal to 80%; the volume ratio of H2 and CO is 1.5% to 4%; the oxidation degree is less than or equal to 10%, and the oxidation degree is calculated according to the following formula:
[0029] Oxidation degree = V1 / V2,
[0030] In the formula, V1 refers to the total volume of CO2 and H2O in the reducing gas, and V2 refers to the total volume of CO and H2 in the reducing gas.
[0031] The present invention also provides a method for producing high-titanium slag using titanium-rich direct reduced iron, comprising: smelting the titanium-rich direct reduced iron produced by the method described above in an electric furnace to obtain molten iron and high-titanium slag, and the TiO2 content of the obtained high-titanium slag is greater than or equal to 70% by mass.
[0032] As described above, the method of producing titanium-rich direct-reduced iron using vanadium-titanium magnetite of the present invention has the following beneficial effects:
[0033] The method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite provided by the present invention is different from the process flow of separately smelting vanadium-titanium iron concentrate powder and titanium concentrate powder obtained after grinding and selection of conventional vanadium-titanium magnetite ore. The two are first mixed to prepare iron-titanium concentrate composite high-titanium pellets that meet the requirements of gas-based vertical furnace direct reduction smelting, and then used in gas-based vertical furnace direct reduction to produce titanium-rich direct reduced iron, achieving a metallization rate of ≥85%, and providing high-quality titanium-rich raw materials for smelting electric furnace titanium slag; subsequently, the prepared titanium-rich direct reduced iron is used for electric furnace smelting to obtain high-titanium slag with TiO2≥70%, which is suitable for producing titanium dioxide, thereby effectively solving the problem of low titanium resource recovery rate in existing vanadium-titanium magnetite. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It shows a process flow diagram of the method for producing titanium-rich direct-reduced iron using vanadium-titanium magnetite in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0035] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0036] In the present invention, unless otherwise specified, the term "plurality" means two or more.
[0037] The character " / " indicates that the objects before and after are in an "or" relationship. For example, A / B means: A or B.
[0038] The term "and / or" is a description of the association relationship between objects, indicating that three relationships can exist. For example, A and / or B means: A or B, or, A and B.
[0039] An embodiment of the present invention provides a method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite, comprising the following steps:
[0040] 1) Preparation of ferro-titanium concentrate composite high-titanium pellets:
[0041] The vanadium-titanium magnetite ore is made into vanadium-titanium iron concentrate powder and titanium concentrate powder;
[0042] The vanadium-titanium iron concentrate powder and the titanium concentrate powder are mixed with a binder to prepare iron-titanium concentrate composite green balls, and then oxidatively roasted to obtain iron-titanium concentrate composite high-titanium balls;
[0043] The compressive strength of the ferro-titanium concentrate composite high-titanium pellets is greater than 2000N / piece, and the reduction expansion rate is less than 20%;
[0044] 2) Direct reduction of ferro-titanium concentrate composite high-titanium pellets:
[0045] The ferro-titanium concentrate composite high-titanium pellets are subjected to a gas-based vertical furnace direct reduction process to obtain titanium-rich direct reduced iron with a metallization rate of ≥85%.
[0046] The method provided in the above-mentioned embodiment of the present invention first prepares vanadium-titanium magnetite into vanadium-titanium iron concentrate powder and titanium concentrate powder, and then mixes them with a binder to prepare iron-titanium concentrate composite green balls, and then obtains iron-titanium concentrate composite high-titanium balls with a compressive strength of >2000N / piece and a reduction expansion rate of <20% through oxidative roasting. The iron-titanium concentrate composite high-titanium balls meet the requirements of direct reduction smelting in a gas-based vertical furnace, and are applied to the direct reduction in a gas-based vertical furnace to produce titanium-rich direct reduced iron, which can achieve a metallization rate of ≥85%, and provide high-quality titanium-rich raw materials for smelting electric furnace titanium slag; subsequently, the obtained titanium-rich direct reduced iron is used for electric furnace smelting to obtain high-titanium slag with TiO2≥70%, which is suitable for the production of titanium dioxide, thereby effectively solving the problem of low titanium resource recovery rate in the existing vanadium-titanium magnetite.
[0047] In addition, compared with the prior art (such as CN107058727A, CN103361481A, CN109136588A, CN101575677A), the method provided by the above embodiment of the present invention also has the following advantages:
[0048] 1. The obtained ferro-titanium concentrate composite high-titanium pellets have a higher TiO2 content than the pellets directly produced from vanadium-titanium magnetite, which can provide high-quality titanium-rich raw materials for the subsequent smelting of titanium slag in electric furnaces, thereby improving the grade of TiO2 in electric furnace smelting titanium slag.
[0049] 2. The vanadium-titanium iron concentrate powder and titanium concentrate powder made from vanadium-titanium magnetite ore are mixed to form green balls, which are then oxidatively roasted to obtain iron-titanium concentrate composite high-titanium balls. While obtaining higher-grade electric furnace smelting titanium slag, the titanium resources in the vanadium-titanium iron concentrate can be fully utilized to achieve effective recovery of titanium resources in the vanadium-titanium magnetite ore.
[0050] 3. No carbonaceous reducing agent is added in the preparation of ferro-titanium concentrate composite high-titanium pellets, thereby avoiding the introduction of ash to reduce the grade of titanium slag, causing the titanium slag to form a large amount of glass phase, destroying the activity of the titanium slag, and also avoiding the generation of CO2 pollutants in the pre-reduction process.
[0051] In some embodiments, in step 1), the vanadium-titanium magnetite ore is crushed, ground, and sieved to obtain vanadium-titanium iron ore concentrate powder and titanium concentrate powder.
[0052] In some embodiments, the vanadium-titanium iron concentrate powder meets at least one of the following indicators: by mass fraction, the powder with a particle size of less than 0.074 mm accounts for ≥80%, the total iron content is ≥50%, and the TiO2 content is ≥9%.
[0053] In some embodiments, the titanium concentrate powder meets at least one of the following indicators: by mass fraction, the powder with a particle size of less than 0.074 mm accounts for ≥80%, and the TiO2 content is ≥45%.
[0054] The performance of vanadium-titanium iron concentrate powder and titanium concentrate powder is controlled according to the above indicators, on the one hand, in order to prepare high-quality iron-titanium concentrate composite high-titanium pellets, and on the other hand, it is beneficial to increase the TiO2 content in the prepared iron-titanium concentrate composite high-titanium pellets, thereby obtaining higher-grade electric furnace smelting titanium slag and realizing the effective recovery of titanium resources in the vanadium-titanium magnetite ore.
[0055] In some embodiments, the ferro-titanium concentrate composite green balls meet at least one of the following indicators: by mass fraction, the proportion of particles with a particle size of 8 to 16 mm is ≥ 90%, and the moisture content is 7.5% to 10.5%. Among them, the particle size requirement for the ferro-titanium concentrate composite green balls is conducive to controlling the size of the ferro-titanium concentrate composite high-titanium balls within an appropriate range, and improving the uniformity of the particle size, which is conducive to the full implementation of the subsequent direct reduction reaction; the moisture content control is conducive to ensuring the green balls are agglomerated. If the moisture content is too high, it is not easy to agglomerate. If the moisture content is too low, the green balls are prone to cracking when drying.
[0056] In some embodiments, in step 1), when preparing the iron-titanium concentrate composite green balls, the mass ratio of the vanadium-titanium iron concentrate powder to the titanium concentrate powder is 10-80:20-90.
[0057] In some embodiments, in step 1), when preparing the iron-titanium concentrate composite green balls, the ratio of the total mass of the vanadium-titanium iron concentrate powder and the titanium concentrate powder to the mass of the binder is 100:1-2.
[0058] In some embodiments, in step 1), in the iron-titanium concentrate composite green ball, the mass ratio of the vanadium-titanium iron concentrate powder, the titanium concentrate powder and the binder is 10-80:20-90:1-2.
[0059] In some embodiments, the binder is selected from at least one of an inorganic binder, an organic binder or a composite binder (a composite of organic and inorganic), wherein the inorganic binder includes but is not limited to bentonite, sodium bentonite, calcium bentonite, slaked lime or water glass, etc., the organic binder includes but is not limited to peridot, modified starch, cornmeal, polyacrylamide, hydroxy cellulose, carboxymethyl cellulose, lignin or molasses, etc., and the composite binder is a composite of an inorganic binder and an organic binder.
[0060] In the above embodiment, the mass ratio of vanadium-titanium iron concentrate powder to titanium concentrate powder is controlled according to the above ratio, which can fully utilize the vanadium-titanium iron concentrate powder and titanium concentrate powder made from the vanadium-titanium magnetite ore on the one hand, and ensure the content of TiO2 in the obtained iron-titanium concentrate composite high-titanium pellets on the other hand, thereby obtaining a high-grade electric furnace smelting titanium slag and realizing the effective recovery of titanium resources in the vanadium-titanium magnetite ore. At the same time, the amount of binder is controlled within the above range to avoid the difficulty in obtaining high-strength pellets due to too low a binder amount, and to avoid the adverse effects caused by too much binder.
[0061] In some embodiments, the vanadium-titanium-iron concentrate powder and the titanium concentrate powder are dried before being mixed with the binder to reduce the moisture content of the powder, which is beneficial to shorten the time required for subsequent green ball drying and improve the quality of the pellets; further, in some embodiments, the drying conditions of the vanadium-titanium-iron concentrate powder and the titanium concentrate powder include at least one of the following conditions: a drying temperature of 150 to 300°C and a drying time of 3 to 5 hours.
[0062] In some embodiments, in step 1), the process of oxidatively roasting the ferro-titanium concentrate composite green pellets to obtain ferro-titanium concentrate composite high-titanium pellets includes preheating and roasting steps in sequence.
[0063] Furthermore, in some embodiments, in step 1), the preheating conditions of the ilmenite concentrate composite green balls include at least one of the following conditions: a preheating temperature of 850 to 950° C. and a preheating time of 8 to 25 minutes.
[0064] Furthermore, in some embodiments, in step 1), the roasting conditions of the ilmenite concentrate composite green balls include at least one of the following conditions: a roasting temperature of 1200 to 1350° C., a roasting time of 20 to 50 minutes, and an oxidizing atmosphere.
[0065] In the above embodiment, the oxidation roasting process parameters are controlled according to the above conditions, so as to ensure that the obtained ferro-titanium concentrate high-titanium pellets meet the requirements of gas-based shaft furnace direct reduction smelting.
[0066] In some embodiments, in step 1), before the preheating process, the ferro-titanium concentrate composite green balls are also dried to further reduce the moisture content of the green balls, which is beneficial to shorten the time required for subsequent oxidative roasting, increase production efficiency, and improve the quality of the pellets; further, in some embodiments, the drying conditions of the ferro-titanium concentrate composite green balls include at least one of the following conditions: a drying temperature of 150 to 300°C and a drying time of 2 to 5 hours.
[0067] In some embodiments, in step 1), after roasting, the ferro-titanium concentrate composite high-titanium pellets are obtained by cooling; further, in some embodiments, the cooling method is selected from natural cooling or exhaust cooling, but is not limited thereto.
[0068] In some embodiments, in step 2), the gas-based vertical furnace direct reduction process conditions include at least one of the following conditions: the direct reduction temperature is 950-1050°C, that is, the high-temperature reducing gas temperature is 950-1050°C; the direct reduction time is 3-5 hours.
[0069] In some embodiments, in step 2), the ferro-titanium concentrate composite high-titanium pellets are first subjected to a spraying treatment, and then a gas-based vertical furnace direct reduction process is performed to obtain titanium-rich direct reduced iron with a metallization rate of ≥85%. The main purpose of the spraying treatment is to reduce the adhesion of the pellets in the vertical furnace. Further, in some embodiments, the spraying solution used for the spraying treatment is selected from lime water, but is not limited thereto; wherein the lime water is prepared from lime powder and water, preferably lime water containing 50 to 70 g / L lime powder. Furthermore, in some embodiments, the mass ratio of the lime powder to the ferro-titanium concentrate composite high-titanium pellets is 0.15 to 0.25:100.
[0070] In some embodiments, in step 2), the ferro-titanium concentrate composite high-titanium pellets and reducing gas are subjected to a gas-based vertical furnace direct reduction process to obtain titanium-rich direct reduced iron with a metallization rate of ≥85%.
[0071] Further, in some embodiments, the reducing gas meets at least one of the following indicators: the volume ratio of H2 and CO is ≥80%; the volume ratio of H2 and CO is 1.5% to 4%; the oxidation degree is less than or equal to ≤10%, and the oxidation degree is calculated according to the following formula:
[0072] Oxidation degree = V1 / V2,
[0073] In the formula, V1 refers to the total volume of CO2 and H2O in the reducing gas, and V2 refers to the total volume of CO and H2 in the reducing gas.
[0074] Controlling the reducing gas performance according to the above-mentioned index requirements is beneficial to the subsequent direct reduction reaction, improving the metallization rate of titanium-rich direct reduced iron, and providing high-quality titanium-rich raw materials for smelting titanium slag in the smelting electric furnace.
[0075] Another embodiment of the present invention provides a method for producing high-titanium slag using titanium-rich direct reduced iron, comprising: smelting the titanium-rich direct reduced iron produced by the method described in the above embodiment / example in an electric furnace to obtain molten iron and high-titanium slag, and the TiO2 content of the obtained high-titanium slag is ≥70% by mass, which is suitable for the production of titanium dioxide.
[0076] In addition, it should be noted that the compressive strength, reduction expansion rate, metallization rate, total iron / TiO2 / moisture content, powder / particle ratio, oxidation degree and other indicators mentioned in the present invention can be detected and calculated through conventional or known methods recorded in the prior art, and will not be repeated here; other process parameter conditions and details not mentioned in the method of the present invention can be carried out according to conventional or known methods in the field of metallurgy and ironmaking, and will not be repeated here.
[0077] The following specific examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range according to the description herein, and are not limited to the specific values exemplified below.
[0078] The vanadium-titanium magnetite ores in the following examples are all produced in the Panzhihua area, but are not limited thereto. That is, the present invention does not impose any special restrictions on the origin of the vanadium-titanium magnetite ores, and vanadium-titanium magnetite ores produced in other areas may also be used.
[0079] Example 1
[0080] like Figure 1 As shown, this embodiment provides a method for producing titanium-rich direct reduced iron and high-titanium slag using vanadium-titanium magnetite, comprising the following steps:
[0081] 1) Preparation of ferro-titanium concentrate composite high-titanium pellets:
[0082] The vanadium-titanium magnetite ore was crushed, ground and screened to obtain vanadium-titanium iron concentrate powder and titanium concentrate powder respectively. The main chemical compositions of the obtained vanadium-titanium iron concentrate powder and titanium concentrate powder are shown in Table 1, wherein, by mass fraction, the total iron content of the vanadium-titanium iron concentrate powder is 56.50%, the TiO2 content is 12.53%, and the TiO2 content of the titanium concentrate powder is 48.80%; at the same time, the powder with a particle size of less than 0.074 mm in the obtained vanadium-titanium iron concentrate powder and titanium concentrate powder accounted for 91.3% and 92.1% respectively.
[0083] The vanadium-titanium iron concentrate powder and the titanium concentrate powder were dried at 150°C for 4 hours, and then mixed with sodium-based bentonite as a binder in a mass ratio of 35:65:1.5 to prepare the iron-titanium concentrate composite green balls. The moisture content of the obtained iron-titanium concentrate composite green balls was 9%, and the particle size of 8-16 mm accounted for 92.5%.
[0084] The iron-titanium concentrate composite green pellets were dried at 180°C for 5 hours, preheated at 900°C for 15 minutes, roasted at 1200°C for 20 minutes in an oxidizing atmosphere, and naturally cooled to obtain iron-titanium concentrate composite high-titanium pellets. The obtained iron-titanium concentrate composite high-titanium pellets have a compressive strength of 2364N / piece and a reduction expansion rate of 7.89%.
[0085] 2) Direct reduction of ferro-titanium concentrate composite high-titanium pellets:
[0086] The ferro-titanium concentrate composite high-titanium pellets prepared in step (1) are sprayed with lime water containing 60 g / L lime powder as a spraying solution at a mass ratio of lime powder to ferro-titanium concentrate composite high-titanium pellets of 0.15:100.
[0087] The ferro-titanium concentrate composite high-titanium pellets after spraying treatment were directly reduced with 950°C high-temperature reducing gas in a vertical furnace for 4 hours to obtain titanium-rich direct reduced iron, and the metallization rate of the obtained titanium-rich direct reduced iron was 87.3%. Among them, the effective component H2+CO in the high-temperature reducing gas was 86.5%, the volume ratio of H2 / CO was 1.8, and the oxidation degree was 7.5%.
[0088] The titanium-rich direct reduced iron obtained in step 2) is melted in an electric furnace to obtain high-quality molten iron and high-titanium slag. The TiO2 content of the obtained high-titanium slag is ≥70% by mass, which is suitable for the production of titanium dioxide.
[0089] Table 1 Main chemical compositions of vanadium-titanium iron concentrate powder and titanium concentrate powder obtained in Examples 1 to 3
[0090] composition <![CDATA[TiO2]]> Tf <![CDATA[Fe2O3]]> FeO CaO MgO <![CDATA[V2O5]]> <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MnO P S Titanium concentrate powder 48.80 32.04 5.48 35.89 0.47 5.61 0.11 1.48 0.84 0.549 0.003 0.015 Vanadium titanium iron concentrate powder 12.53 56.50 54.39 23.45 1.25 2.46 0.64 2.36 2.41 0.278 0.002 0.040
[0091] Example 2
[0092] like Figure 1 As shown, this embodiment provides a method for producing titanium-rich direct reduced iron and high-titanium slag using vanadium-titanium magnetite, comprising the following steps:
[0093] 1) Preparation of ferro-titanium concentrate composite high-titanium pellets:
[0094] The vanadium-titanium magnetite ore was crushed, ground and screened to obtain vanadium-titanium iron concentrate powder and titanium concentrate powder respectively. The main chemical compositions of the obtained vanadium-titanium iron concentrate powder and titanium concentrate powder are shown in Table 1, wherein, by mass fraction, the total iron content of the vanadium-titanium iron concentrate powder is 56.50%, the TiO2 content is 12.53%, and the TiO2 content of the titanium concentrate powder is 48.80%; at the same time, the powder with a particle size of less than 0.074 mm in the obtained vanadium-titanium iron concentrate powder and titanium concentrate powder accounts for 92.5% and 91.8% respectively.
[0095] The vanadium-titanium iron concentrate powder and the titanium concentrate powder were dried at 180°C for 3 hours, and then mixed with sodium-based bentonite as a binder in a mass ratio of 25:75:1.8 to prepare the iron-titanium concentrate composite green balls. The moisture content of the obtained iron-titanium concentrate composite green balls was 9.5%, and the particle size of 8-16 mm accounted for 93.2%.
[0096] The ferro-titanium concentrate composite green pellets were dried at 200°C for 4 hours, preheated at 850°C for 10 minutes, roasted at 1250°C for 20 minutes in an oxidizing atmosphere, and naturally cooled to obtain ferro-titanium concentrate composite high-titanium pellets. The obtained ferro-titanium concentrate composite high-titanium pellets have a compressive strength of 2513N / piece and a reduction expansion rate of 7.32%.
[0097] 2) Direct reduction of ferro-titanium concentrate composite high-titanium pellets:
[0098] The ferro-titanium concentrate composite high-titanium pellets prepared in step (1) are sprayed with lime water containing 55 g / L lime powder as a spraying solution at a mass ratio of lime powder to ferro-titanium concentrate composite high-titanium pellets of 0.2:100.
[0099] The ferro-titanium concentrate composite high-titanium pellets after spraying treatment were directly reduced with 1000°C high-temperature reducing gas in a vertical furnace for 3.5 hours to obtain titanium-rich direct reduced iron, and the metallization rate of the obtained titanium-rich direct reduced iron was 86.8%. Among them, the effective component H2+CO in the high-temperature reducing gas was 88%, the volume ratio of H2 / CO was 2.0, and the oxidation degree was 6.8%.
[0100] The titanium-rich direct reduced iron obtained in step 2) is melted in an electric furnace to obtain high-quality molten iron and high-titanium slag. The TiO2 content of the obtained high-titanium slag is ≥70% by mass, which is suitable for the production of titanium dioxide.
[0101] Example 3
[0102] like Figure 1 As shown, this embodiment provides a method for producing titanium-rich direct reduced iron and high-titanium slag using vanadium-titanium magnetite, comprising the following steps:
[0103] 1) Preparation of ferro-titanium concentrate composite high-titanium pellets:
[0104] The vanadium-titanium magnetite ore was crushed, ground and screened to obtain vanadium-titanium iron concentrate powder and titanium concentrate powder respectively. The main chemical compositions of the obtained vanadium-titanium iron concentrate powder and titanium concentrate powder are shown in Table 1, wherein, by mass fraction, the total iron content of the vanadium-titanium iron concentrate powder is 56.50%, the TiO2 content is 12.53%, and the TiO2 content of the titanium concentrate powder is 48.80%; at the same time, the powder with a particle size of less than 0.074 mm in the obtained vanadium-titanium iron concentrate powder and titanium concentrate powder accounted for 90.8% and 91.5% respectively.
[0105] The vanadium-titanium iron concentrate powder and the titanium concentrate powder were dried at 150°C for 4 hours, and then mixed with sodium-based bentonite as a binder in a mass ratio of 15:85:1.9 to prepare the iron-titanium concentrate composite green balls. The obtained iron-titanium concentrate composite green balls have a moisture content of 9%, and particles with a particle size of 8 to 16 mm account for 93.5%.
[0106] The iron-titanium concentrate composite green pellets were dried at 250°C for 4 hours, preheated at 900°C for 15 minutes, roasted at 1250°C for 25 minutes in an oxidizing atmosphere, and naturally cooled to obtain iron-titanium concentrate composite high-titanium pellets. The obtained iron-titanium concentrate composite high-titanium pellets have a compressive strength of 2213N / piece and a reduction expansion rate of 8.14%.
[0107] 2) Direct reduction of ferro-titanium concentrate composite high-titanium pellets:
[0108] The ferro-titanium concentrate composite high-titanium pellets prepared in step (1) are sprayed with lime water containing 60 g / L lime powder as a spraying solution at a mass ratio of lime powder to ferro-titanium concentrate composite high-titanium pellets of 0.2:100.
[0109] The ferro-titanium concentrate composite high-titanium pellets after spraying treatment were directly reduced with 1025°C high-temperature reducing gas in a vertical furnace for 4 hours to obtain titanium-rich direct reduced iron, and the metallization rate of the obtained titanium-rich direct reduced iron was 86.5%. Among them, the effective component H2+CO in the high-temperature reducing gas was 90%, the volume ratio of H2 / CO was 2.0, and the oxidation degree was 7.0%.
[0110] The titanium-rich direct reduced iron obtained in step 2) is melted in an electric furnace to obtain high-quality molten iron and high-titanium slag. The TiO2 content of the obtained high-titanium slag is ≥70% by mass, which is suitable for the production of titanium dioxide.
[0111] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite, characterized in that: The following steps are involved: 1) Preparation of ferro-titanium concentrate composite high-titanium pellets: The vanadium-titanium magnetite ore is made into vanadium-titanium iron concentrate powder and titanium concentrate powder; The vanadium-titanium iron concentrate powder and the titanium concentrate powder are mixed with a binder to prepare iron-titanium concentrate composite green balls, and then oxidatively roasted to obtain iron-titanium concentrate composite high-titanium balls; The compressive strength of the ferro-titanium concentrate composite high-titanium pellets is greater than 2000N / piece, and the reduction expansion rate is less than 20%; 2) Direct reduction of ferro-titanium concentrate composite high-titanium pellets: The ferro-titanium concentrate composite high-titanium pellets are subjected to a gas-based vertical furnace direct reduction process to obtain titanium-rich direct reduced iron with a metallization rate greater than or equal to 85%.
2. The method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite according to claim 1, characterized in that: In step 1), the vanadium-titanium magnetite ore is crushed, ground, and sieved to obtain vanadium-titanium-iron concentrate powder and titanium concentrate powder; And / or, the vanadium-titanium iron ore concentrate powder satisfies at least one of the following indicators (A1) to (A3): (A1) By mass fraction, the proportion of powder with a particle size less than 0.074 mm is greater than or equal to 80%; (A2) The total iron content is greater than or equal to 50% by mass; (A3) TiO2 content is greater than or equal to 9% by mass; And / or, the titanium concentrate powder satisfies at least one of the following indicators (B1) to (B2): (B1) By mass fraction, the powder with a particle size less than 0.074 mm accounts for greater than or equal to 80%; (B2) TiO2 content is greater than or equal to 45% by mass; And / or, the ferro-titanium concentrate composite green ball meets at least one of the following indicators (C1) to (C2): (C1) The moisture content is 7.5% to 10.5% by mass; (C2) The proportion of particles with a particle size of 8 to 16 mm is greater than or equal to 90%.
3. The method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite according to claim 1 or 2, characterized in that: In step 1), when preparing the iron-titanium concentrate composite green ball, the mass ratio of the vanadium-titanium iron concentrate powder to the titanium concentrate powder is 10-80:20-90; And / or, in step 1), when preparing the iron-titanium concentrate composite green balls, the ratio of the total mass of the vanadium-titanium iron concentrate powder and the titanium concentrate powder to the mass of the binder is 100:1-2.
4. The method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite according to claim 1, characterized in that: In step 1), the vanadium-titanium-iron concentrate powder and the titanium concentrate powder are dried before being mixed with the binder; And / or, in step 1), the process of oxidative roasting of the ferro-titanium concentrate composite green pellets to obtain ferro-titanium concentrate composite high-titanium pellets includes preheating and roasting steps in sequence.
5. The method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite according to claim 4, characterized in that: The drying conditions of the vanadium-titanium iron concentrate powder and the titanium concentrate powder include at least one of the following conditions (a1) to (a2): (a1) drying temperature is 150 to 300°C; (a2) Drying time is 3 to 5 hours; And / or, the preheating conditions of the ferro-titanium concentrate composite green balls include at least one of the following conditions (b1) to (b2): (b1) preheating temperature is 850-950°C; (b2) Preheating time is 8 to 25 minutes; And / or, the roasting conditions of the ferro-titanium concentrate composite green balls include at least one of the following conditions (c1) to (c2): (c1) the calcination temperature is 1200 to 1350° C.; (c2) calcination time is 20 to 50 minutes; (c3) The calcination atmosphere is an oxidizing atmosphere.
6. The method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite according to claim 4 or 5, characterized in that: In step 1), before the preheating process, the ferro-titanium concentrate composite green balls are dried; And / or, in step 1), after roasting, the ferro-titanium concentrate composite high-titanium pellets are obtained by cooling.
7. The method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite according to claim 6, characterized in that: The drying conditions of the ferro-titanium concentrate composite green balls include at least one of the following conditions (d1) to (d2): (d1) drying temperature is 150 to 300°C; (d2) Drying time is 2 to 5 hours; And / or, the cooling method is selected from natural cooling or exhaust cooling.
8. The method for producing titanium-rich direct-reduced iron using vanadium-titanium magnetite according to claim 1, characterized in that: Step 2) The process conditions include at least one of the following conditions (e1) to (e4): (e1) Direct reduction temperature is 950-1050°C; (e2) direct reduction time is 3 to 5 hours; (e3) the ferro-titanium concentrate composite high-titanium pellets are first subjected to a spraying treatment, and then subjected to a gas-based vertical furnace direct reduction process to obtain titanium-rich direct reduced iron having a metallization rate greater than or equal to 85%; (e4) The ferro-titanium concentrate composite high-titanium pellets and reducing gas are subjected to a gas-based vertical furnace direct reduction process to obtain titanium-rich direct reduced iron with a metallization rate greater than or equal to 85%.
9. The method for producing titanium-rich direct reduced iron using vanadium-titanium magnetite according to claim 8, characterized in that: In step 2), the reducing gas satisfies at least one of the following indicators (D1) to (D3): (D1) The volume percentage of H2 and CO is greater than or equal to 80%; (D2) The volume ratio of H2 and CO is 1.5% to 4%; (D3) The degree of oxidation is less than or equal to 10%, and the degree of oxidation is calculated according to the following formula: Oxidation degree = V1 / V2, In the formula, V1 refers to the total volume of CO2 and H2O in the reducing gas, and V2 refers to the total volume of CO and H2 in the reducing gas.
10. A method for producing high-titanium slag by direct reduction of titanium-rich iron, characterized in that: include: The titanium-rich direct reduced iron produced by the method according to any one of claims 1 to 9 is smelted in an electric furnace to obtain molten iron and high-titanium slag, and the TiO2 content of the high-titanium slag is greater than or equal to 70% by mass.
Citation Information
Patent Citations
Method for producing titanium-rich materials and steel products through titanium mine
CN101575677A
Preparation method for vanadium-titanium-iron concentrate magnetized pellets for shaft furnace
CN103361481A
Preparation method of vanadium titanomagnetite oxidized pellet for gas base shaft furnace
CN107058727A
Method for preparing high-titanium slag by directly reducing titanium concentrate in gas-based shaft furnace
CN109136588A
Cited By
Preparation method and application of high-titanium schreyerite raw material for hydrogen-based shaft furnace
CN120464851A
Gas-based low-carbon reduced iron process for electric heating rotary kiln
CN122503563A
Electric heating shaft furnace carbon-based low-carbon reduced iron technological process
CN122521938A
Carbon-based low-carbon reduced iron process for electric heating rotary kiln
CN122588300A
Low-carbon titanium-iron separation process for high-titanium and low-iron iron ore
CN122686885A